Health Science Library System University of Pittsburgh, USA - Lapo ( Лапо ), Piotr ( Пeтр ); Dautova ( Даутова ), Anar ( Анар ) (My University, 2015)
The presentation highlights design and equipment of the University of Pittsburgh Library System including the central Hillman Library and Falk Library of the Health Sciences and the Carnegie-Mellon University Library (Pittsburgh, USA) В презентации освещены некоторые детали интерьера и оборудования библиотечной системы Университета Питтсбурга (включая центральную библиотеку имени Хиллмана и медицинскую библиотечную систему имени Фалка), а также библиотечную систему Университета Карнеги-Меллона (г.Питтсбург, США)
Медицинская библиотечная система Университета Питтсбурга (США)
Keywords: academic library; library design and equipment; medical library